If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(1x + 8) = 12 Reorder the terms: 2(8 + 1x) = 12 (8 * 2 + 1x * 2) = 12 (16 + 2x) = 12 Solving 16 + 2x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16' to each side of the equation. 16 + -16 + 2x = 12 + -16 Combine like terms: 16 + -16 = 0 0 + 2x = 12 + -16 2x = 12 + -16 Combine like terms: 12 + -16 = -4 2x = -4 Divide each side by '2'. x = -2 Simplifying x = -2
| 6x^2-12=5x^2-4x | | X/12=34 | | -1x+12-3x=-5(x-2)+2 | | 18y^2-7y-2=0 | | 4x-x+9=(x+2)+p | | g(-1)forg(t)=(t^2-1)(t+4) | | 4n-2=4n-6 | | -2x+11-3x=-5(x-2)+2 | | 4+77x=44x+16 | | X-(-8)=15.6 | | 2x+6=-22-5x | | -2x+12-3x=-5(x-2)+2 | | 5(-3+6x)=-15 | | -1/3-g=-1/3 | | 8w-17w=18 | | 3e^2x+5=15 | | 10m+6=76 | | X-(5x+2)=2 | | 36a^2+120a+64=0 | | 63=54 | | 81c^3+90c^2+25c=0 | | 7x-5=-7x-5 | | 2x-5/3=5/6 | | x+5=0.5(2x-7) | | 5(x+11)=5(21-x) | | 54=3(2-2x) | | X*X*Y*Y=1600 | | x+4=0.6(2x-7) | | tn=tn-1+6 | | h(6)ifh(x)=x^2-2x-5 | | 8x+9-7x=11 | | 7(3x-9)=-63 |